Observation of a refractory metal matrix containing Zr-Ti-rich precipitates in a Mo0.5NbTa0.5TiZr high entropy alloy. (15th April 2020) - Whitfield, T.E.; Pickering, E.J.; Talbot, C.E.; Jones, C.N.; Stone, H.J.; Jones, N.G.
Abstract: Refractory metal high entropy superalloys (RMHES) offer potentially superior strength at elevated temperatures and lower densities than Ni-based superalloys. However, concerns exist over their ductility as their microstructures comprise fine distributions of refractory metal solid solution precipitates within a Zr- and Ti-rich ordered matrix. Consequently, identifying methodologies to invert this arrangement is critical. Here, we show that removal of Al from the AlMo0.5 NbTa0.5 TiZr RMHES, enables a microstructure to be obtained comprising Zr-Ti-rich disordered precipitates within a refractory metal matrix. This observation represents a significant development for the field and may help guide future alloy design. Graphical abstract: Image, graphical abstract